1984
DOI: 10.1126/science.6610213
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Neurotoxicity of 1-Methyl-4-Phenyl-1,2,5,6-Tetrahydropyridine in Mice

Abstract: 1-Methyl-4-phenyl-1,2,5,6- tetrahydropyri dine ( MPTP ) is known to cause an irreversible destruction of the dopaminergic nigrostriatal pathway and symptoms of parkinsonism in humans and in monkeys. However, MPTP has been reported to act only minimally or not at all in several other animal species. When MPTP (30 milligrams per kilogram of body weight) was administered parenterally to mice, a decrease in concentrations of neostriatal dopamine and its metabolites, a decrease in the capacity of neostriatal synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
318
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 984 publications
(338 citation statements)
references
References 6 publications
17
318
0
3
Order By: Relevance
“…Furthermore, ten days after the insult, the absence of TH-positive cell bodies most likely represents a loss of cells, rather than a mere downregulation of tyrosine hydroxylase (Jackson-Lewis, et al, 1995). The finding of reduced TH-positive neurons in the myenteric ganglia in the absence of any effect on cholinergic or nitric oxide neurons confirms that MPTP is selectively toxic to dopamine neurons in the ENS, much as it is in the brain (Bove, et al, 2005, Heikkila, et al, 1984, Jackson-Lewis, et al, 1995). Our results suggest that nigral and enteric dopamine neurons exhibit grossly similar levels of sensitivity to parenteral MPTP, but the relative vulnerability between gut and brain dopamine neurons is difficult to assess.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, ten days after the insult, the absence of TH-positive cell bodies most likely represents a loss of cells, rather than a mere downregulation of tyrosine hydroxylase (Jackson-Lewis, et al, 1995). The finding of reduced TH-positive neurons in the myenteric ganglia in the absence of any effect on cholinergic or nitric oxide neurons confirms that MPTP is selectively toxic to dopamine neurons in the ENS, much as it is in the brain (Bove, et al, 2005, Heikkila, et al, 1984, Jackson-Lewis, et al, 1995). Our results suggest that nigral and enteric dopamine neurons exhibit grossly similar levels of sensitivity to parenteral MPTP, but the relative vulnerability between gut and brain dopamine neurons is difficult to assess.…”
Section: Discussionmentioning
confidence: 78%
“…The dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine [MPTP] is known to induce parkinsonism in hu-mans, primates, and mice ( [27,90,132,133]). MPTP is converted by astrocytes to the metabolite 1 methyl-4-phenylpyridinium [MPP + ], a substrate of the DA transporter ( [40,41]).…”
Section: Animal Models Of Parkinson's Diseasementioning
confidence: 99%
“…review [1] we summarized how the sudden appearance of parkinsonism in relatively young patients in the San Francisco Bay Area in 1982 was traced to their use of a designer drug, 'new heroin', manufactured by a clandestine laboratory, and to the MPTP contained in defective batches of the street drug. Almost immediately following the reports that MPTP is neurotoxic to humans [2], subhuman primates md mice [3][4][5], eliciting damage to dopaminergic aeurons, it was shown that MPP + (1-methyl-4-phenylpyridinium) is the neurotoxic form and that it arises by 4-e oxidation of MPTP in brain mitochondria [6]. Proof that the enzyme responsible for processing MPTP is monoamine oxidase (MAO B) in the glial cells, of which it is an excellent substrate and that MAO A also oxidizes MPTP, albeit more slowly, was reported soon thereafter [7].…”
Section: Introductionmentioning
confidence: 99%